الاستجواب كآلية للمعارضة وعلاقته بالأداء الوظيفي للمؤسسة البرلمانية -دراسة ميدانية بالبرلمان الجزائري عهدة 2012/2017 - بوترعه, بلال; بوقروز, أمينة (جامعة الوادي University of Eloued, 2018)
ملــــخـــص: إن المؤسسة البرلمانية بمهامها التشريعية تسعى إلى الكمال في أدائها الوظيفي بتناسق أفرادها ووحدة برامجها، للسهر على تحقيق المشاريع التنموية من جهة ولتمثيل المجتمع في رغباته واحتياجاته من جهة أخرى. لكن نشأة المعارضة في البرلمان، بتصورها المختلف في تسيير البلاد، وباختلاف نظرتها مع السلطة في قضايا معينة، وبوضعها لبرامج متباينة، يولد قطبية ثنائية داخل المؤسسة ينشا من خلالها الصراع التنظيمي وتستخدم فيه المعارضة أهم آلية وهي الاستجواب البرلماني للحكومة بأجهزتها ووزرائها كوسيلة حادة وفاعلة للرقابة البرلمانية. abstract: The parliamentary institution, with its legislative functions, seeks to achieve perfection in its job performance by coordinating its members and its program unit to ensure the realization of developmental projects on the one hand and to represent society in its desires and needs on the other hand. But the emergence of the opposition in parliament, in its different perception of the country's administration, and its different views with the authority on certain issues, and its development of different programs, generates a bilateral polarization within the institution through which the organizational conflict arises and where the opposition uses the most important mechanism: parliamentary questioning of the government with its organs and ministers as a sharp and effective means of parliamentary oversight .Keywords: Parliament, Interrogation, Functionality, Opposition.
Keywords: البرلمان، الاستجواب، الأداء الوظيفي، المعارضة